Comunicación organizacional y satisfacción de los colaboradores de la empresa Triplay Martin S.A.C. Iquitos 2020 - Alemán Pardo, Guiliana Marisela (2022)
The situation of the study is to determine the relationship between organizational communication and job satisfaction in the company Triplay Martin S.A.C. Iquitos – 2020. Poor organizational communication represented by the company's employees, as related to the level of job satisfaction; The question of the problem is what is the relationship between organizational communication and job satisfaction in the employees of the company Triplay Martin S.A.C. Iquitos, 2020? The study is quantitative, descriptive, correlational, which had a sample of 50 workers of the company who met the requirements stipulated for its analysis. In the collection of the data, the survey and the questionnaire instrument were used. For the processing of the information, the Excel program was used, and the results through tables and graphs. At the end of this study, it was concluded that the measured indicators, referring to internal communication, integration, veracity, commitment, fulfillment and safety, were measured as expected, where 74% of the study population said they agreed with the significant relationship between the indicators as fundamental factors for obtaining job satisfaction.